Analysis of Earth Dam Break of a Reservoir Based on BREACH Model - LIU Fengru; ZHAO Yuhao; ZHAN Damei (Renmin Zhujiang, 2021)
Frequent rain and flood may lead to earth dam break,resulting in serious consequences.Therefore,it is necessary to analyze the dam break and its impact.Based on the BREACH model,this paper studies the earth dam break of a reservoir.The results show that:in the piping dam break mode,with the increase of flood magnitude,the maximum breach discharge,final breach width and cumulative discharge also increase.Under the same flood magnitude,the maximum breach discharge and final average breach width of overtopping dam break are large,and the relative risk is great.In the given scheme,the earthquake emergency is safer than that in other schemes.In addition,the cumulative discharge is equal to the sum of initial storage capacity and inflow volume,which verifies the rationality of the calculation results from the model.